Pengaruh Perilaku Fear Of Missing Out (FOMO) Dan Literasi Keuangan Terhadap Keputusan Investasi Mahasiswa Program Studi Administrasi Bisnis Di STIA Malang - Sanjaya, Aprillina; Tsabita, Ifarza; Sabella A.F., Shelly; Salsabilla F.L., Khumaira; Mandur, Dionisius (JOURNAL AKSES STIA MALANG, 2025)
The advancement of technology and the widespread use of social media have contributed to the rising participation of young people, particularly Generation Z, in digital investment activities. However, this trend also presents challenges such as impulsive investment decisions driven by social influence and limited financial understanding. This study aims to examine the influence of Fear of Missing Out (FOMO) behavior and financial literacy on the investment decisions of students in the Business Administration Study Program at STIA Malang. A quantitative approach was used, employing survey techniques with structured questionnaires distributed to 59 respondents. Data analysis included validity and reliability tests, classical assumption testing, and multiple linear regression analysis. The results indicate that both FOMO and financial literacy significantly influence investment decisions, both partially and simultaneously. The R square value of 0.440 suggests that these two independent variables explain 44% of the variation in students’ investment decisions. These findings emphasize the importance of financial education and awareness of social influence in shaping prudent investment behavior. Kata Kunci: FOMO; generation Z; investment decision; financial literacy